2019
DOI: 10.1111/tmi.13232
|View full text |Cite
|
Sign up to set email alerts
|

BCG scar, socioeconomic and nutritional status: a study of newborns in urban area of Makassar, Indonesia

Abstract: SummaryObjectiveTo investigate factors that determine the response to Bacille Calmette–Guérin (BCG) vaccination in urban environments with respect to socioeconomic status (SES), prenatal exposure to infections or newborn's nutritional status.MethodsThe study was conducted in an urban area, in Makassar, Indonesia. At baseline, 100 mother and newborns pair from high and low SES communities were included. Intestinal protozoa, soil transmitted helminths, total IgE, anti‐Hepatitis A Virus IgG and anti‐Toxoplasma Ig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Some indicated that low SES is associated with small scar size. 12 In this study the reverse is true. Where the higher severity and mortality were associated with high socioeconomic status and small size BCG scar.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Some indicated that low SES is associated with small scar size. 12 In this study the reverse is true. Where the higher severity and mortality were associated with high socioeconomic status and small size BCG scar.…”
Section: Discussionmentioning
confidence: 73%
“…The SES is mainly detected by several variables where occupation, income and education are important determinants. 12…”
Section: Introductionmentioning
confidence: 99%
“…However, scars may be present or not after the BCG vaccine. Scars may be absent due to administrating lower doses of vaccine in childhood, the difficulty of injecting the entire amount of vaccine and the relatively weak local immune response in young children, or the probability that they may even disappear with time [5] , [6] , [7] .…”
Section: Discussionmentioning
confidence: 99%
“…33 The results of this study are in line with previous studies, which stated that gender and nutritional status of children were not associated with BCG scars. 34 In the study of Amaruddin et al (2019), it was shown that there was a significant relationship between socioeconomic status and the nutritional status of infants at birth with BCG scars after controlling for leptin levels. 35 BCG scars are a sign of better survival among children in countries with high child mortality.…”
Section: Factors Associated With Scar Bcgmentioning
confidence: 99%
“…34 In the study of Amaruddin et al (2019), it was shown that there was a significant relationship between socioeconomic status and the nutritional status of infants at birth with BCG scars after controlling for leptin levels. 35 BCG scars are a sign of better survival among children in countries with high child mortality. BCG vaccination could affect the response to several major infections, one of that also includes malaria.…”
Section: Factors Associated With Scar Bcgmentioning
confidence: 99%